Bending behaviour of corroded RC continuous beams with C-FRCM strengthening system. (15th November 2022) - Feng, Ran; Liu, Panpan; Zhang, Jingzhou; Wang, Fangying; Xu, Ying; Zhu, Ji-Hua
Abstract: This paper presents a numerical investigation into the bending behaviour of uncorroded and corroded reinforced concrete (RC) continuous beams with a strengthening system. Finite element analysis (FEA) was performed on ten RC beams considering interface performance, including five uncorroded and five corroded beams. The cracks development, bending capacities and load-displacement curves of the simulated RC beams in the loading process were validated against those from tests. Then, a parametric study including 35 RC beam models, considering the effects of carbon-fabric (CF) mesh layer, complete wrapping layer and the degree of corrosion of steel bar on their bending capacities, was conducted. Ductility and strengthening effects of specimens were discussed in the parametric study. It can be found that the carbon-fabric reinforced cementitious matrix (C-FRCM) strengthening system can improve the bending capacities of the corroded RC beams. As the layer of CF mesh increases, the ductility of the specimen decreases. The combined use of the C-FRCM plate and the complete wrapping as the end anchorage enhanced the ultimate loads of RC beams to a greater extent than those strengthened with C-FRCM plate only. The applicability of current design codes for RC beams with C-FRCM strengthening system was examined through comparisons of the bending capacity predictions of RC beams with those obtained from tests and numerical analyses. It was found that European Code (FIB Bulletin 14) provides more accurate predictions than American Specifications (ACI 549.4R-20, AC 434-0616-R1, ACI 440.2R-17) and Chinese Code (CECS 146–2003 (2007)). Therefore, design modifications based on the most accurate design rule of FIB Bulletin 14 were made. By utilizing regression analysis on the numerical results, the formula for bending capacities of the examined RC beams was proposed and showed improved accuracy. Highlights: FEA was carried out on corroded RC continuous beams with C-FRCM strengthening system. The effects of CF mesh layer, complete wrapping layer and degree of corrosion were evaluated. The current design codes generally provide quite conservative estimations on the bending capacities. FIB Bulletin 14 is relatively conservative compared with other design codes. The proposed formula provides more accurate estimations on the bending capacities.